International research in agriculture - Addeke H Boerma; Robert S McNamara; Rudolph A Peterson (New York: Consultative Group on International Agricultural Research, 1974)
This publication describes the purposes, structure and operations of the Consultative Group on International Agricultural Research (CGIAR) and the international research and training programmes (10) which it supports
lje 29/06/17
Loans
Keywords: Agriculture---Research